2001
DOI: 10.1063/1.1416474
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the native Cr2O3 oxide surface of CrO2

Abstract: Using photoemission and inverse photoemission, we have been able to characterize the Cr2O3 oxide surface of CrO2 thin films. The Cr2O3 surface oxide exhibits a band gap of about 3 eV, although the bulk CrO2 is conducting. The thickness of this insulating Cr2O3 layer is twice the photoelectron escape depth which is about 2 nm thick. The effective Cr2O3 surface layer Debye temperature, describing motion normal to the surface, is about 370 K. From a comparison of CrO2 films grown by different techniques, with dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
47
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(53 citation statements)
references
References 30 publications
6
47
0
Order By: Relevance
“…2. In the inset we show the resistance of the samples prepared in the same fashion from pure MgB 2 (which has a superconducting transition of around 37 K), and pure CrO 2 whose resistance is fairly ‡at except for the lowest temperatures, where the activation type behavior is observed, due to the presence of a nm thick Cr 2 O 3 insulating layer at the surface of CrO 2 [18] . The resistance of the composite samples is low for pure ate composition range 0:35 < x < 0:5, with the low-temperature peak value of the resistance about three orders of magnitude higher than that of pure CrO 2 sample.…”
mentioning
confidence: 99%
“…2. In the inset we show the resistance of the samples prepared in the same fashion from pure MgB 2 (which has a superconducting transition of around 37 K), and pure CrO 2 whose resistance is fairly ‡at except for the lowest temperatures, where the activation type behavior is observed, due to the presence of a nm thick Cr 2 O 3 insulating layer at the surface of CrO 2 [18] . The resistance of the composite samples is low for pure ate composition range 0:35 < x < 0:5, with the low-temperature peak value of the resistance about three orders of magnitude higher than that of pure CrO 2 sample.…”
mentioning
confidence: 99%
“…For a clean Cr 2 O 3 /CrO 2 surface ͑zero monolayers Co coverage͒, the spectrum is the typical Cr 2 O 3 /CrO 2 valence-band spectrum. 5,18 With increasing Co coverage, the bands at 4 to 8 eV from Cr-O 2p hybridization bands, and the band at 2 eV binding energy dominated by the Cr 3d orbitals, are suppressed while a strong feature at about 1 eV becomes very prominent and the density of states at Fermi energy is increasingly well established. At Co coverages above 15 ML, the overlapping Co 3d bands around 1 eV binding energy are dominant and show the sharp Fermi edge characteristic of a metal.…”
mentioning
confidence: 99%
“…5,18,20 From the outset, i.e., from the initial stages of surface preparation, the core-level binding energies indicated that the stable surfaces were Cr 2 O 3 . X-ray photoemission ͑XPS͒ measurements were obtained using the Mg K␣ line radiation ͑1253.6 eV͒.…”
mentioning
confidence: 99%
See 2 more Smart Citations